Serum Cotinine Levels and Prehypertension in Never Smokers. (17th February 2013) - Alshaarawy, Omayma; Xiao, Jie; Andrew, Michael E.; Burchfiel, Cecil; Shankar, Anoop
Abstract : Background . Few studies have shown that self-reported secondhand smoke exposure in never smokers is associated with high blood pressure. However, there are no studies investigating the relationship between secondhand smoke exposure, measured objectively by serum cotinine levels, and high blood pressure in never smokers. Methods . We examined never smokers (n = 2027 ) from the National Health and Nutrition Examination Survey 2005–2008. Our exposure of interest was the secondhand smoke exposure estimated by serum cotinine level and our outcome was prehypertension (n = 734 ), defined as a systolic blood pressure of 120–139 mmHg or diastolic blood pressure of 80–89 mmHg. Results . We found that, in never smokers, serum cotinine levels were positively associated with prehypertension. Compared to those with cotinine levels in the lowest quartile (≤0.024 ng/mL), the multivariable odds ratio (95% confidence interval) of prehypertension among those with cotinine levels in the highest quartile (≥0.224 ng/mL) was 1.45(1.00, 2.11); P trend = 0.0451 . In subsequent subgroup analyses, the positive association was found to be stronger among men, non-Whites, and non-obese subjects. Conclusion . Higher secondhand smoke exposure measured objectively by serum cotinine levels was found to be associated with prehypertension in certain subgroups of a representative sample of the US population.